Implementasi Metode Overall Equipment Effectiveness Berbasis Six Big Losses Guna Mengevaluasi Efektivitas Mesin Packing Semen - Septia Priambodo; Nina Aini Mahbubah (Fakultas Teknik, 2021)
Integrated maintenance management is an important factor in maintaining the stability of machine operations in manufacturing companies. PT AAAA Factory Gresik is a cement manufacturing company, where the Section Division of Gresik Finish Mill Packer Operation has a problem of downtime cement packing machine 40 kg and causes production delay. This study aims to evaluate the effectiveness of the 40kg cement packing machine as well as to calculate losses due to unproductiveness of the packing machine. Overall Equipment Effectiveness (OEE), Six Big Losses, and Failure Mode and Effect Analysis (FMEA) were used as research method. This study found that OEE value for January-December 2019 of 41.25% are considered as lower percentage in compare with the ideal value of international standards which is 85%. Moreover, the largest average losses are found, namely reduce speed losses, idle and stoppages minor losses and defects in process with percentage in following order, 4.49%, 4.49% and 2.76%.Result from FMEA analysis have been identified 3 highest Risk Priority Number (RPN), namely transportation with an RPN value of 294, the second RPN value of 288 is a blockage in the packing machine, finally the engine button is jammed with an RPN value of 252. The proposed improvement scenario is the start of the engine operating operators checking and cleaning machines regularly and the marketing division expands the sales market.